Hyperpolarized [1-13C]Pyruvate Magnetic Resonance Spectroscopic Imaging for Evaluation of Early Response to Tyrosine Kinase Inhibition Therapy in Gastric Cancer. - Esfahani, Shadi A.; Callahan, Cody; Rotile, Nicholas J.; Heidari, Pedram; Mahmood, Umar; Caravan, Peter D.; Grant, Aaron K.; Yen, Yi-Fen (Molecular Imaging & Biology, 2022)
Purpose: To evaluate the use of hyperpolarized [1-13C]pyruvate magnetic resonance spectroscopic imaging (HP-13C MRSI) for quantitative measurement of early changes in glycolytic metabolism and its ability to predict response to pan-tyrosine kinase inhibitor (Pan-TKI) therapy in gastric cancer (GCa).Procedures: Pan-TKI afatinib-sensitive NCI-N87 and resistant SNU16 human GCa cells were assessed for GLUT1, hexokinase-II (HKII), lactate dehydrogenase (LDHA), phosphorylated AKT (pAKT), and phosphorylated MAPK (pMAPK) at 0-72 h of treatment with 0.1 μM afatinib. Subcutaneous NCI-N87 tumor-bearing nude mice underwent [18F]FDG PET/MRI and HP-13C MRSI at baseline and 4 days after treatment with afatinib 10 mg/kg/day or vehicle (n = 10/group). Changes in PET and HP-13C MRSI metabolic parameters were compared between the two groups. Imaging findings were correlated with tumor growth and histopathology over 3 weeks of treatment.Results: In vitro analysis showed a continuous decrease in LDHA, pAKT, and pMAPK in NCI-N87 compared to SNU16 cells within 72 h of treatment with afatinib, without a significant change in GLUT1 and HKII in either cell type. [18F]FDG PET of NCI-N87 tumors showed no significant change in PET measures at baseline and day 4 of treatment in either treatment group (SUVmean day 4/day 0: 2.7 ± 0.42/2.34 ± 0.38, p = 0.57 in the treated group vs. 1.73 ± 0.66/2.24 ± 0.43, p = 0.4 in the control group). HP-13C MRSI demonstrated significantly decreased lactate-to-pyruvate ratio (L/P) in treated tumors (L/P day 4/day 0: 0.83 ± 0.30/1.10 ± 0.20, p = 0.012 vs. 0.94 ± 0.20/0.98 ± 0.30, p = 0.75, in the treated vs. control group, respectively). Response to afatinib was confirmed with decreased tumor size over 3 weeks (11.10 ± 16.50 vs. 293.00 ± 79.30 mm3, p < 0.001, treated group vs. control group, respectively) and histopathologic evaluation.Conclusions: HP-13C MRSI is a more representative biomarker of early metabolic changes in response to pan-TKI in GCa than [18F]FDG PET and could be used for early prediction of response to targeted therapies.